Características da comercialização de cacau na Bahia - Martins Rezende , Alberto; Aad Neto , Alexandre; Fagundes de Sousa , Antônio; Estrela Barroco , Hélio; Brandt, Sérgio Alberto (Revista Ceres, 2025)
The general objective of this study is to analyse the system of the commercialization of cocoa in the municipio of Ilhéus, Bahia. Specifically, it aims to identify the various channels of cocoa commercialization and to quantify the amount of the respective contributions by the participants in the market. The data were obtained by interviewing cocoa producers who were stratified in the sample according to the volume of their production and the exporters of cocoa. The analysis uses the funtional and institutional market methods as a theoretical base.